Growth Inhibition and Proline Accumulation in Canavalia ensiformis under Salinity Stress - Sri Mulyaningsih; Sifa Arofah; Rifaatul Muthmainnah (UNIVERSITAS PGRI MADIUN, 2026)
Jack bean (Canavalia ensiformis L.) is a legume with considerable potential as an alternative food source due to its high protein and carbohydrate content and its ability to improve soil fertility. However, its cultivation remains limited, particularly on marginal lands such as saline soils that are increasingly expanding due to seawater intrusion and improper irrigation. Soil salinity inhibits plant growth by causing osmotic and ionic stress while triggering proline accumulation as a physiological adaptation. This study aimed to evaluate the effects of salinity stress (NaCl) on the morphological growth and proline content of jack bean plants. The experiment was conducted in Singkup Village, Pasirwangi District, Garut, from April 26 to June 10, 2025, using a Completely Randomized Design (CRD) with five NaCl concentrations (0, 1500, 2500, 3500, and 5000 ppm) and five replications. Observed parameters included plant height, leaf number, root length, fresh weight, and proline content. Analysis of variance (ANOVA) showed that NaCl significantly affected all growth parameters. Growth inhibition was most pronounced at 5000 ppm, whereas optimal growth occurred at 0 ppm. Conversely, proline content increased with higher NaCl concentrations, indicating the plant’s adaptive response to salinity stress. Overall, jack bean growth declined significantly at NaCl levels above 2500 ppm, accompanied by increased proline accumulation. These findings provide insights for developing legume cultivation strategies on saline soils